Medium Access Control Techniques for Massive Machine-Type Communications in Cellular Networks - Astudillo, Carlos A.; Fonseca, Nelson L. S. da (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2023)
A key component of the Internet of things (IoT) ecosystem is wide-area network connectivity, for which cellular network technologies are a promising option through their support of massive machine-type communication (mMTC). However, numerous devices transmitting sporadically small data packets in a highly synchronized way can generate overload on the radio access network, leading to a shortage of resources, especially those associated with the random access procedure, such as orthogonal preambles and control and data resources. This paper summarizes the main contributions of the first author’s doctoral dissertation supervised by the second author. The dissertation proposes medium access control (MAC) techniques for addressing problems related to the support of mMTC in cellular networks. Results show that the proposals support quality of service (QoS), decrease access latency, decrease the device energy consumption, and increase the probability of successful channel access and resource utilization under massive random access.